The Great War in history : debates and controversies, 1914 to the present - Winter, J. M. (Studies in the social and cultural history of modern warfare ;, 2005)
Since the Armistice, a vast literature has been produced on the First World War. This is a comparative analysis of the ways in which this history has been written. It identifies three generations of historians, film directors and writers who have provided military, social and cultural interpretations of the war.